Inflections of the Bayesian Paradigm in Perceptual Psychology. (December 2016) - Burigana, Luigi; Vicovaro, Michele
Bayesian modeling has gained a conspicuous position in contemporary perceptual psychology. It can be examined from two viewpoints: a formal one, concerning the logical attributes of and the algebraic operations on the components of the models, and a substantive one, concerning the empirical meaning of those components. We maintain that, while there is homogeneity between Bayesian models of visual perception in their formal setup, remarkable differences can be found in their substantive aspect, that is, how the question "Where do probabilities come from?" is answered when designing the models. In particular, we focus on an inflection that we call "congenial" because it consistently embodies the inversion idea of the Bayes' rule in terms of optical inversion and highlight delicate issues that face this inflection for a consistent realization of the scientific program it represents. We also suggest ideas concerning the organization of the Bayesian area within perceptual psychology, which appears variegated, with the congenial inflection in a central position, and a fringe of disputable classification along the border.